Effects of the Oral Antidiabetic Repaglinide on the Reproduction of Rats - Viertel, Bruno; Güttner, Jürgen (Arzneimittelforschung, 2000)
Repaglinide (CAS 135062-02-1), a biguanide, is an orally available insulin secretagogue (ß-cell stimulant) and has been developed for the treatment of Type II diabetes. The developmental toxicity of the compound was investigated in rats. The effects on fertility, on embryo- and fetogenesis and on peri- and postnatal development were investigated. In a ‘fertility study’ 24 males were treated with 0, 1, 30, 300 mg/kg for 10 weeks prior to mating and during mating, and 24 females with 0, 1, 30, 80 mg/kg for 4 weeks prior to mating until gestation day 22 (hysterectomy group) or through gestation day 22 until postnatal day, i.e. lactation day 21 (littering group). In a ‘teratogenicity study’ with a hysterectomy group and a littering group included, 36 females were treated with 0, 0.5, 5 and 80 mg/kg from gestation day 7-16. In a ‘peri-postnatal study’ with a cross-foster group included 23 females were treated in the core study with 0, 0.5, 5, 30 and 80 mg/kg from gestation day 16 to lactation day 21 and in the cross-foster group 18 females with 0 and 80 mg/kg from gestation day 16 to lactation day 21. In a ‘supplementary study’ with five treatment windows 13 females each were treated with 80/ 30 mg/kg from gestation day 1-5 (W 1), gestation day 6-16 (W 2), gestation day 17-22 (W 3), lactation day 1-14 (W 4) and lactation day 15-21 (W 5). Effects of repaglinide on fertility, implantation, early and late embryogenesis, fetogenesis, birth and postnatal development including fertility of the offspring were investigated. In the ‘fertility study’ the NOTEL (no toxic effect level) for males was estimated to be 1 mg/kg and for females 30 mg/kg. In the ‘teratogenicity study’ the maternal NOTEL was 0.5 mg/kg as it was in the ‘peri-postnatal study’ 5 mg/kg. Food consumption and body weight gain of females were significantly reduced at the beginning of the respective treatment periods of the ‘supplementary study’ indicating a strong reaction of the dams to the treatment underlined by the death of individual animals (W 3, W 4 and W 5). Offspring survival during the last trimester of pregnancy and during lactation was affected in the ‘fertility study’ and in the ‘peri-postnatal study’after 30 and 80 mg/kg and in the ‘supplementary study’ slightly in W 3 and more pronounced in W 4 and W 5. Changes of the skeleton in the extremities of the offspring were observed in all studies where the animals were exposed to repaglinide during late pregnancy (i.e. after completion of organogenesis) and/or lactation. At radiography the skeletal alterations comprised deformities of the coracoid process and acromion process, of the proximal humeral epiphysis, and of the epiphysis distalis and the condylus distalis of the femur. Deltoids of the humerus showed a slight increase of height and a length reduction. The radius and ulna were slightly bent. The most marked effects and the highest incidence were induced during the first half of lactation (W 4). As age of offspring increased the changes were more pronounced and occurred with a higher incidence. Correspondingly, ash weight, calcium, magnesium and phosphorus content of bones were reduced, but the proportions remained constant. Histopathological examination (supplementary study) showed that small fibrotic foci were formed in the area of dislocation of parts of the epiphyseal plate and that the remaining hyaline cartilage was thinner than normal (W 3, W 4 and W 5). Additionally, the longitudinal axis of the diaphysis juxtaposed to the growth zone was markedly bent, becoming convex to the lateral side.The studies clearly demonstrated that long bone development was not impaired during embryogenesis and early fetogenesis but after completition of organogenesis exclusively, indicating that repaglinide was not teratogenic. Effects of repaglinide were clearly effects on growth. The effects seen in all studies only occurred at excessively high plasma concentrations which will not be reached at human therapeutic doses.
Keywords: Biguanide; CAS 135062-02-1; Long bone deformities; Non-teratogenic growth effect; Pancreatic ß-cell stimulating oral antidiabetic; Repaglinide, reproduction studies